2018
DOI: 10.1002/gch2.201800012
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Producing Interdisciplinary Knowledge and Action for Sustainable Water Governance: Lessons from the Development of a Water Resources Decision Support System in Pernambuco, Brazil

Abstract: One of the most pressing global challenges for sustainable development is freshwater management. Sustainable water governance requires interdisciplinary knowledge about environmental and social processes as well as participatory strategies that bring scientists, managers, policymakers, and other stakeholders together to cooperatively produce knowledge and solutions, promote social learning, and build enduring institutional capacity. Cooperative production of knowledge and action is designed to enhance the like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…[5] simulates typical 24-hour storm events, providing a reference for model application. In Brazil, the works of [11], [12] and [6] applied the WRF-Hydro model in Brazilian watersheds.…”
Section: International Symposium On Innovation and Technology (Siintec)mentioning
confidence: 99%
“…[5] simulates typical 24-hour storm events, providing a reference for model application. In Brazil, the works of [11], [12] and [6] applied the WRF-Hydro model in Brazilian watersheds.…”
Section: International Symposium On Innovation and Technology (Siintec)mentioning
confidence: 99%
“…Part of the contributions focused on large scale systems and water supply reservoirs in the northeast region. White et al (2018) presented lessons from the development of a decisionmaking system of water management for the Pernambuco state, including reservoir operation, flood forecast, and scenario analyses on a web system. Gomes et al (2019a) showed the optimization of Cruzeta water supply reservoir in Piancó-Piranhas-Açu rivers and how the operational rules can decrease the failure rate of priority water demands.…”
Section: Operation Of Reservoirs and Systems Of Reservoirsmentioning
confidence: 99%
“…Discrepancies in the treatment of scale can be addressed firstly by developing a shared understanding of the system(s) being analyzed through a holistic interdisciplinary process ( Thompson, 2009 ; White et al, 2019 ). There is increasing recognition that holistic approaches are necessary to enable an integrated assessment of scale issues in socio-environmental (social-ecological) systems ( Schlüter et al, 2019a , 2019b ; Hoekstra et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Central to this interdisciplinary lens is making concrete the multidimensional nature of scale issues and the interplay among these. Here, the term “interdisciplinary” is favored over trans- or multi-disciplinary as the focus is on the “blending” of disciplinary knowledge ( White et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%